The Boutique of the Master Perfumer: Drama and its accessibility for blind and low vision individual (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article investigated the Drama process The Boutique of the Master Perfumer, analyzing its potential as a pedagogical-creative approach accessible to blind or visually impaired individuals. The experience, conducted within a university extension project, highlighted the mobilization of tactile worldview in theatrical training and creation. The results indicated that Drama can challenge theater’s visual-centric nature and foster interactions among participants with different sensory perceptions. Furthermore, they reinforced the importance of Extension as a privileged space for dialogue between higher education students and visually impaired individuals, historically marginalized in academic settings.
Keywords: drama; tactile worldseeing; theatrical accessibility; visual impairment; university extension